THE IMPACT OF CRYPTO FRAUD ON THE DIGITAL ECONOMY: INCREASE IN LOSSES AND THE ROLE OF CYBERSECURITY IN RISK MINIMIZATION (INNOVATIVE ECONOMY, 2025)
Semenchenko N.V., Melnychuk V.E., Kalinichenko M.S. THE IMPACT OF CRYPTO FRAUD ON THE DIGITAL ECONOMY: INCREASE IN LOSSES AND THE ROLE OF CYBERSECURITY IN RISK MINIMIZATION  Purpose. The aim of this article is to study the impact of crypto fraud on the digital economy, as well as to analyse ways to minimize risks by implementing innovative cybersecurity solutions.Methodology of research. The study uses a combination of analytical and empirical methods to study the impact of crypto fraud on the digital economy. Data from reputable financial and cybersecurity sources such as Chainalysis, CoinDesk, and Forbes are created to estimate financial losses caused by fraud. Statistical analysis is used to study cryptocurrency fraud trends over the past years.Findings. Types of crypto fraud are considered, such as phishing, market manipulation, investment fraud schemes, and wallet hacking. It is found that these actions lead to significant financial losses, reduce trust in digital assets, and destabilize the investment climate. Innovative approaches to minimizing risks are analysed, including using artificial intelligence to analyse transactions and behavioural patterns of users. It is found that systems based on machine learning technologies allow the detection of anomalous actions in real time and activate additional protection measures, which increases security in the cryptocurrency sector. Solutions aimed at reducing economic losses and protecting investors are proposed, which increases confidence in cryptocurrency technologies. Artificial intelligence allows for more effective combat against crypto fraud and ensures the stability of the digital asset market.Originality. The economic impact of crypto fraud is substantiated for the first time, highlighting the need for AI-driven cybersecurity measures. It is established that the use of a multi-layered strategy that combines regulatory policy, technological progress and information campaigns will help reduce risks in the crypto-asset sector. The key role of artificial intelligence in detecting fraudulent activities and strengthening trust in the cryptocurrency ecosystem is proven.Practical value. The study results have significant practical value for regulatory authorities, financial institutions, investors and developers of cybersecurity technologies. The proposed measures to minimize crypto fraud can be used to improve the regulatory and legal framework in the digital economy and cryptocurrency regulation. Also, the practical significance of the study is impossible in forming recommendations for business and crypto exchanges on the implementation of advanced technological solutions in the security field. The revealed patterns of fraud growth can help develop strategies to protect investors and ensure the financial stability of the cryptocurrency market.Key words: cryptocurrency, fraud, artificial intelligence, economic security, digital economy.
Keywords: cryptocurrency; fraud; artificial intelligence; economic security; digital economy.